Factors Influencing Online Impulse Buying Behavior: Evidence from Shopee Live - Syakhira Iswan, Zahra; Roostika, Ratna (Universitas Ahmad Dahlan, 2025)
This study aims to investigate the factors that influence online impulse buying behavior among Indonesian consumers on the Shopee Live e-commerce platform. With the advent of digital technology, shopping behavior has shifted significantly towards online platforms, particularly through innovative features such as live streaming. Utilizing a purposive sampling technique, data was collected from Shopee users through a Google Forms and analyzed using Structural Equation Modeling (SEM). The research findings revealed that factors such as time pressure, quantity pressure, and social influence did not significantly influence enjoyment leading to the absence of impulse buying online. Whereas the results of economic benefits, visual elements and sound elements on enjoyment were highly significant which played an important role in driving impulse purchase decisions. This suggests that consumers are more attracted to tangible economic benefits such as discounts and attractive visual and sound ornament presentations during live streaming sessions. The study concludes that enhancing these key visual and economic factors can effectively increase impulse buying behavior, offering valuable insights for retailers and marketers looking to optimize their strategies in a live commerce environment.